Enhancing the Solubility, Dissolution Rate and Oral Bioavailability of Poorly Water-soluble Drug, Satranidazole by Solid Dispersion prepared by using β-Cyclodextrin as a Carrier (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present work aims to prepare and characterize solid dispersions of Santranidazole using β-Cyclodextrin to improve its aqueous solubility and dissolution with the aid of solvent evaporation technique. Solid dispersions showed marked improvement in the solubility behavior and stepped forward for drug launch. From all the formulations, F2 becomes an optimized method based on the characterization, solubility and dissolution studies. The enhancement of dissolution depends upon the nature and quantity of the carrier. The rise in the dissolution rate may be attributed to; the reduced particle size of drug deposited at the carrier’s floor and the enhanced wet capacity of the drug debris by the carrier. The optimized formulations have been evaluated through Differential Scanning Calorimetry (DSC), Fourier remodel infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM).